Effects of different high‐pressure syntheses on the magnetization reversal properties of Bi2FeMnO6 ceramics. Issue 4 (13th April 2022) - Chen, Zipeng; Liu, Ronggang; Ma, Zhengzheng; Du, Jianhua; Li, Kun; Chen, Yi; Wang, Yi
Abstract: Bi2 FeMnO6 ceramics were prepared under atmospheric pressure and a high pressure of 1–6 GPa. The effects of different high‐pressure syntheses on the microstructures were analyzed by X‐ray diffraction and Rietveld refinement, scanning electron microscopy–energy‐dispersive spectroscopy, X‐ray photoelectron spectrometer, and Raman spectroscopy test. The temperature dependence of magnetization was systematically investigated for all samples. There was a transition from rhombohedral R 3 c structure to orthorhombic phase Pnam with increasing synthetic pressure. The samples synthesized under atmospheric pressure are rhombohedral R 3 c with antiferromagnetic (AFM) magnetic temperature ( M – T curves). The samples synthesized under a high pressure of 5–6 GPa are orthorhombic phase Pnam with the magnetization reversal effect, whereas the lower high‐pressure (1–3 GPa) synthesized samples might be in the transitional area between them. This structural transformation is accompanied by the transformation from normal AFM M – T curves to a typical magnetization reversal effect. The relationship between the lattice distortion and the internal magnetic competition mechanism of the material was discussed. The existence of magnetization reversal in these systems may ascribe to the competition between the single‐ion magnetic anisotropy and the Dzyaloshinsky–Moriya interaction.